2021
DOI: 10.3390/ijms222111960
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and Functional Analysis of microRNA Deregulation in Cancer-Associated Fibroblasts in Oral Squamous Cell Carcinoma Depicts an Anti-Invasive Role of microRNA-204 via Regulation of Their Motility

Abstract: Background: Knowledge on the role of miR changes in tumor stroma for cancer progression is limited. This study aimed to investigate the role of miR dysregulation in cancer-associated fibroblasts (CAFs) in oral squamous cell carcinoma (OSCC). Methodology: CAF and normal oral fibroblasts (NOFs) were isolated from biopsies of OSCC patients and healthy individuals after informed consent and grown in 3D collagen gels. Total RNA was extracted. Global miR expression was profiled using Illumina version 2 panels. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…RBC-EV miR-204 decreased cell viability, mitigated cell migration, and suppressed spheroid formation and growth, more strongly against MYCN-amp NB cells, but these anti-neuroblastoma effects were also observed, but to a lesser extent, in MYCN-NA cells (Figures 5-7). These results are consistent with previous evidence, in which miR-204 exhibited anticancer activities against several cancers with diversed oncogenic backgrounds, i.e., oral squamous cell carcinoma (OSCC), renal cell carcinoma, and non-small-cell lung cancer [47][48][49][50]. As RBC-EV miR-204 could inhibit both NB cell migration and spheroid formation and growth, the use of RBC-EV miR-204 as an adjuvant therapy may mitigate metastasis in high-risk neuroblastoma, regardless MYCN amplification status.…”
Section: Discussionsupporting
confidence: 93%
“…RBC-EV miR-204 decreased cell viability, mitigated cell migration, and suppressed spheroid formation and growth, more strongly against MYCN-amp NB cells, but these anti-neuroblastoma effects were also observed, but to a lesser extent, in MYCN-NA cells (Figures 5-7). These results are consistent with previous evidence, in which miR-204 exhibited anticancer activities against several cancers with diversed oncogenic backgrounds, i.e., oral squamous cell carcinoma (OSCC), renal cell carcinoma, and non-small-cell lung cancer [47][48][49][50]. As RBC-EV miR-204 could inhibit both NB cell migration and spheroid formation and growth, the use of RBC-EV miR-204 as an adjuvant therapy may mitigate metastasis in high-risk neuroblastoma, regardless MYCN amplification status.…”
Section: Discussionsupporting
confidence: 93%
“…Cancer-associated fibroblasts (CAFs) are one major sub-cell type within the tumor microenvironment that has drawn attention. Multiple studies have confirmed that the increasing presence of CAFs associates poorly with prognosis in lung, prostate, and oral cancer (Knops et al, 2020;Rajthala et al, 2021;Wu et al, 2021). Specifically, CAFs are reported to promote cell proliferation, regulate immune responses, remodel ECM, and induce drug resistance by cytokine and metabolite secretion as well as extracellular vesicle transfer (Gieniec et al, 2019;Levi-Galibov et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…mir-34a-5p expression is significantly decreased in CAFs, resulting in a loss of its tumor suppressive effect [ 120 ]. The expression of miR-204 in cancer-adjacent fibroblasts also inhibits tumors by suppressing fibroblast migration by modulating the expression of signaling molecules and by directly targeting integrin α11 (ITGA11) and is also downregulated in HNSSC of the oral cavity [ 121 ].…”
Section: Normal Tissue Fibroblastsmentioning
confidence: 99%